We Don't Need No Education: A Textual Analysis of Anglo-American Popular Music Lyrics about School - Avery Barnes; Isaac Calvert (MDPI AG, 2023)
This paper investigates how popular music lyrics over the past century have described the nature and dynamics of Anglo-American student experience in formal schooling contexts. Using data from a cross-section of music streaming service databases, we identified 131 popular songs whose lyrics specifically discuss dimensions of formal school experience, especially from a student perspective. After three rounds of inductive thematic textual analysis, 7 major themes with 28 associated sub-themes emerged. These themes include school environment, situated feelings about school, negative results of school, school and society, conformity, negative view of teachers and the sexualization of teachers. Based on the assumption that a song owes at least some of its popularity to the appeal and relatability of its lyrical content to its audience, we hope that an in-depth, thematic analysis of such lyrics will give educationalists new insight into Anglo-American school experience through the salient societal medium of popular music. We further hope that these lyrical themes will shed new light on the lived experiences of school-age students and thereby deepen educationalists' understanding of student experiences, perceptions and dispositions toward school more generally.